Analisis kritis konstruktif praksis teologi publik Gereja Masehi Injili Halmahera di era otonomi daerah - Mojau, Julianus (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2021)
This paper highlights the praxis of public theology that resulted from the decisions of the Synod of the Evangelical Christian Church in Halmahera (GMIH Synod) in the context of the era of regional autonomy during the 2002-2017 ministry period. By using qualitative research methods through library research, this analysis examines theological discourse and living church praxis as stated in the decisions of the GMIH Synod. Starting from the analysis of the social function of the Church emphasized by Ricardo F. Nanuru and the praxis of inter-religious advocate public theology by Felix Wilfred, this study found that: (a) GMIH ecclesiastical documents have seeded the praxis of interreligious public theology in the form of a series of pastoral recommendations and information on the Church's social services; (b this interreligious public theology advocacy practice needs to have an adequate theological basis and a measurable translation into the practice of living in the GMIH church. This theologically measured programmatic integration helps GMIH demonstrate its ecclesiastical identity as a social-humanist-ecological body of Christ that has an impact on Halmahera's public sphere in the era of regional autonomy which is being overshadowed by the neo-liberal economy and the extractive and exploitive mining economy.  AbstrakTulisan ini menyoroti praxis teologi publik hasil keputusan-keputusan persidangan Sinode Gereja Masehi Injili di Halmahera (Sinode GMIH) dalam konteks otonomi daerah selama periode pelayanan 2002-2017. Dengan meng-gunakan metode penelitian kualitatif melalui jenis penelitian kepustakaan, analisis ini mengkaji wacana teologis dan praxis hidup seperti tertuang dalam keputusan-keputusan Sidang Sinode GMIH. Bertolak dari analisis fungsi sosial Gereja yang ditekankan oleh Ricardo F. Nanuru dan praxis teologi publik advo-katif intereligius Felix Wilfred kajian ini menghasilkan: (a) dokumen-dokumen gerejawi GMIH telah membenihkan praxis teologi publik intereligius dalam bentuk serangkaian anjuran pastoral dan informasi pelayanan sosial Gereja; (b) praxis advokasi teologi publik interreligious ini perlu mendapat pendasaran teo-logis yang memadai dan penerjemahannya yang terukur dalam praktik hidup menggereja GMIH. Pengintegrasian programatis terukur secara teologis ini membantu GMIH meragakan identitas eklesialnya sebagai tubuh sosial-huma-nis-ekologis Kristus yang berdampak dalam ruang publik Halmahera di era otonomi daerah yang sedang dibayang-bayangi oleh ekonomi neo-liberal dan ekonomi pertambangan ekstraktif dan eksploitatif.